Water, sanitation, and hygiene in selected health facilities in Ethiopia: risks for healthcare acquired antimicrobial-resistant infections - Teshome Bekele Elema; Abebe Aseffa Negeri; Lavuun Verstraete; Adey Feleke Desta; Taha Al-Mulla; Kitka Goyol; Kaleab Baye; Kaleab Baye (Frontiers Media S.A., 2024)
BackgroundInadequate water, sanitation and hygiene (WASH) in health facilities, and the low adherence to infection control protocols can increase the risk of hospital-acquired (nosocomial) infections (HAIs). The risk for HAIs can increase morbidity, and mortality, health care cost, but also contribute to increased microbial resistance.ObjectivesThe study aimed to assess WASH facilities and practices, and levels of nosocomial pathogens in selected health facilities in Oromia Region and Southern, Nations and Nationalities and Peoples (SNNPs) Region.Materials and methodsAn observational cross-sectional study design was employed to assess the WASH facilities in health care in SNNPs (Bulle and Doyogena) and Oromia (Bidre) regions through interviews and direct observations (n = 26 facilities). Water and surface samples were collected from major hospitals and health centers. A total of 90 surface swabs and 14 water samples were collected identified, characterized and tested for antimicrobial susceptibility. Epi-info was used for data entry and the data was subsequently exported to Stata version 17 for data cleaning and analysis.ResultsWater supply, toilet facilities, and waste management procedures were suboptimal (below the minimum standards of WHO). Only 11/26 of the health facilities had access to water at the time of the survey. The lowest hand-hygiene compliance was for Bidre (4%), followed by Doyogena (14%), and Bulle (36%). Over 70% of the identified bacteria were from four categories: Staphylococcus spp., Bacillus spp., E. coli, and Klebsiella spp. These bacteria also found in high-risk locations including neonatal intensive care units, delivery and surgical rooms. Antimicrobial susceptibility detected in ≥50% of the isolates for penicillin, cefazolin, ampicillin, oxacillin, and cotrimoxazole, and ≥ 50% of the isolates displayed multi-drug resistance.ConclusionInvesting in WASH infrastructures, promotion of handwashing practices, implementing infection prevention and control (IPC) measures and antibiotic stewardship is critical to ensure quality care in these settings. We recommend careful use of higher generation cephalosporins and fluoroquinolones.